2007
DOI: 10.1523/jneurosci.3165-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Recent History of Stimulus Speeds Affects the Speed Tuning of Neurons in Area MT

Abstract: Visual motion processing plays a key role in enabling primates' successful interaction with their dynamic environments. Although in natural environments the speed of visual stimuli continuously varies, speed tuning of neurons in the prototypical motion area MT has traditionally been assessed with stimuli that moved at constant speeds. We investigated whether the representation of speed in a continuously varying stimulus context differs from the representation of constant speeds. We recorded from individual MT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Similar effects have been observed with fMRI, suggesting priming related effects caused by the recent stimulus presentations (Moore and Engel, 2001). Adapted fMRI responses observed when repeating a stimulus have been attributed to reduction in the gain of the underlying neural response and/or retuning of the neural response (GrillSpector et al, 2006;Krekelberg et al, 2006;Schlack et al, 2007). The 4 s adaptation period used in our study (Fang et al, 2005), and the repulsive aftereffects we observe (Klink et al, 2008), are most consistent with a gain change interpretation of fMRI adaptation.…”
Section: Adaptation To Depth Structurementioning
confidence: 99%
“…Similar effects have been observed with fMRI, suggesting priming related effects caused by the recent stimulus presentations (Moore and Engel, 2001). Adapted fMRI responses observed when repeating a stimulus have been attributed to reduction in the gain of the underlying neural response and/or retuning of the neural response (GrillSpector et al, 2006;Krekelberg et al, 2006;Schlack et al, 2007). The 4 s adaptation period used in our study (Fang et al, 2005), and the repulsive aftereffects we observe (Klink et al, 2008), are most consistent with a gain change interpretation of fMRI adaptation.…”
Section: Adaptation To Depth Structurementioning
confidence: 99%
“…The neural underpinnings of visual motion processing for constant speed targets have been studied extensively both in the monkey and man (for reviews, see Born and Bradley 2005;Orban et al 2003). Less is known about the brain substrates of kinematic estimates when the target speed changes continuously (Lisberger and Movshon 1999; Price et al 2005;Schlack et al 2007). In particular, target objects are frequently accelerated by Earth gravity (1g ϭ 9.81 m/s 2 ), as in free-fall or projectile motion.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this poor perceptual sensitivity, the motor system does not seem to take into account unpredictable accelerations of a target in timing manual interceptions; instead, the latter are geared to target direction and speed (Engel and Soechting 2000;Port et al 1997;Senot et al 2003). Also, electrophysiological studies in the monkey showed that most neurons in a key visual-motion area, the middle temporal (MT) area, are tuned to direction and speed but not to acceleration, although an acceleration signal can be reconstructed from their population response (Lisberger and Movshon 1999;Price et al 2005;Schlack et al 2007). Neural responses to acceleration or deceleration in MT may be explained by speed-dependent adaptation rather than by an explicit code for acceleration/deceleration (Schlack et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MT, on the other hand, responsivity is reduced most strongly for stimuli that differ from the adapter. As a result, tuning shifts toward the adapter (Kohn and Movshon 2004; Krekelberg et al 2006b; Schlack et al 2007). …”
mentioning
confidence: 99%